Types Of Realities Found In Elementary School Textbooks And Teaching Methods (Journal of Pedagogical Inventions and Practices, 2025)
The importance of realities in education, their role in improving educational quality, and their ability to connect students' knowledge with real life are discussed. It highlights how realities help students understand cultural heritage and national values, as well as develop critical and creative thinking skills. The types of realities in elementary school textbooks are analyzed, including cultural and national realities, natural and geographical realities, historical and folklore realities, and linguistic realities. Methods of teaching realities are explored, such as interactive methods (discussions, role-playing games, group activities), practical activities (preparing national dishes, handicrafts), text analysis, and written assignments (essay writing, storytelling), as well as using pictures and videos for explanation. The impact of realities on students is also examined, including the development of cultural awareness, adaptation to social life, the formation of ecological and economic thinking, and guidance in career choice.